The role of domestic finishes, furnishings and objects in constructing feminine identities - Armada, Hannah Abigail Y.
The purpose of this study was to explore how finishes, furnishings, and objects construct feminine identities in the living rooms of selected middle class Filipino households. A post structuralist research design was employed which involved data collection through visual documentation and interviews. Purposive sampling was used to select the five (5) participants composed of wives and mothers; their respective living rooms were the subjects of this thesis. The instrumentation used in the study included an interview guide, an iPad voice recording application, anecdotal forms, a pen, and a camera phone. Coding methods were used to analyze the data. The results revealed that the finishes, furnishings, and objects used in the selected living rooms expressed the participant's preferences, personality, roles, and memories. The participants were mostly involved in the living room arrangement and decoration through the purchase, arrangement, maintenance/upkeep, and use of materials and objects. Each of them experienced a certain degree of authority full control, partial control, or minimal control-over the arrangement and decoration of the living room. The participant's interest, husband's interest, and husband's profession were factors that affected the involvement and authority of the participants. Through the color, material, style, and layout of finishes, furnishings, and objects in the living room, the feminine identities of the self, the wife, the mother, and the working woman were constructed in the domestic interior.